Gtsf1 is essential for proper female sex determination and transposon silencing in the silkworm, Bombyx mori - Chen, Kai (PLoS Genet, 2020)
Sex determination pathways are astoundingly diverse in insects. For instance, the silk moth Bombyx mori uniquely use various components of the piRNA pathway to produce the Fem signal for specification of the female fate. In this study, we identified BmGTSF1 as a novel piRNA factor which participates in B. mori sex determination. We found that BmGtsf1 has a distinct expression pattern compared to Drosophila and mouse. CRISPR/Cas9 induced mutation in BmGtsf1 resulted in partial sex reversal in genotypically female animals by shifting expression of the downstream targets BmMasc and Bmdsx to the male pattern. As levels of Fem piRNAs were substantially reduced in female mutants, we concluded that BmGtsf1 plays a critical role in the biogenesis of the feminizing signal. We also demonstrated that BmGTSF1 physically interacted with BmSIWI, a protein previously reported to be involved in female sex determination, indicating BmGTSF1 function as the cofactor of BmSIWI. BmGtsf1 mutation resulted in piRNA pathway dysregulation, including piRNA biogenesis defects and transposon derepression, suggesting BmGtsf1 is also a piRNA factor in the silkworm. Furthermore, we found that BmGtsf1 mutation leads to gametogenesis defects in both male and female. Our data suggested that BmGtsf1 is a new component involved in the sex determination pathway in B. mori.